Addiction to Inflation or to Fiscal Deficits? the Chilean Experience of 1970s - Caputo-Galarce, R (John Wiley and Sons Ltd, 2022)
Latin America is a region with very high income inequality and low social mobility. It has experienced several stagnation episodes and was plagued, from the mid-1970s to the early 2000s, by hyperinflation. This phenomenon took place at different moments in time and with varying intensity. Using a novel data set for Chile, we identify the main drivers of fiscal reforms and seigniorage shocks that were crucial for inflation dynamics. We conclude that inflation, after the military coup that deposed Allende s socialist government, was used to finance defence spending non-explicitly considered in the official figures. We interpret these fiscal expenditures as seigniorage shocks. Hence, the Chilean economy was addicted to fiscal deficits for most of the 1970s. Addiction to inflation, in the form of destabilizing inflation expectations that evolved independently of the level of seignorage, was not relevant. © 2020 John Wiley & Sons, Ltd.